KAJIAN LINGKUNGAN BIOTIK DAN ABIOTIK CENDANA (Santalum album L.) DALAM KAWASAN HUTAN KEMASYARAKATAN DAN DI LUAR KAWASAN DI KABUPATEN TIMOR TENGAH SELATAN - Sarah Kahi Timba; L. Michael Riwu Kaho; W. I. I. Mella (Partner, 2021)
This study was to determine the biotic and abiotic environment of sandalwood (Santalum album L.) in the community forest area and outside the area in Timor Tengah Selatan Regency using a completely randomized block design (RALB) with 4 treatments (area with sandalwood (P1), area without sandalwood (P2), outside area with sandalwood (P3) and outside area without sandalwood (P4)) at altitudes of 0-300 mdpl, 300-600 mdpl, 600-900 mdpl and <1200 mdpl. The results showed that the differences in community forest areas and non-areas had a significant effect on the diversity of vegetation but soil chemical properties did not significantly affect the differences. Differences in and outside the area show more of the obstacles that exist in a land for certain uses. So that the diversity of vegetation and soil is an independent variable that is not at all influenced by differences in the location of the area and outside the area. Key Words: sandalwood (Santalum ablum L), biotic, abiotic, host and altitude